INTENTIONAL STRUCTURAL MODIFICATION OF PHRASEOLOGICAL UNITS AS A LINGUOPOETIC PHENOMENON (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article investigates the purposeful structural disruption of stable combinations (phraseological units, proverbs, and idioms) in literary texts as a linguopoetic phenomenon. The study examines the essence, artistic functions, and linguistic significance of this phenomenon. Through analytical examples, it is demonstrated that the conscious alteration of stable combination structures serves as a decisive means of expressing authorial intent, enriching layers of meaning, and influencing the reader.
Keywords: stable combinations, phraseology, linguopoetics, structural transformation, literary text, idiom, stylistic device.